2013
DOI: 10.1097/aap.0b013e318289e922
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Spine Disease Is a Risk Factor for Persistent Phrenic Nerve Paresis Following Interscalene Nerve Block

Abstract: The use of interscalene blocks (ISBs) for shoulder surgery improves postoperative pain control, reduces recovery room times, and reduces overall hospital stays. The most common and potentially disabling adverse effect associated with ISBs is phrenic nerve paresis. Fortunately, persistent phrenic nerve paresis (PPNP) is rare. There are only 4 case reports of PPNP in the English literature. At our institution, we identified 9 cases of PPNP over a 9-year period, representing an incidence of 1 (0.048%) in 2069. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…[17][18][19] The use of lower volumes of local anesthetic in ultrasound-guided interscalene block has been shown to reduce, but not eliminate, the incidence of phrenic nerve palsy. 3,4 This is not surprising given that the phrenic nerve lies within 2 mm Fig.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] The use of lower volumes of local anesthetic in ultrasound-guided interscalene block has been shown to reduce, but not eliminate, the incidence of phrenic nerve palsy. 3,4 This is not surprising given that the phrenic nerve lies within 2 mm Fig.…”
Section: Discussionmentioning
confidence: 99%
“…[68] The incidence of persistent HDP following ISB for shoulder surgery is of 1 per 2069 (0.048%). [9] …”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that symptomatic cervical spine disease was a risk factor of persistent HDP following ISB. [9] …”
Section: Discussionmentioning
confidence: 99%
“…4 Sympatholysis and antagonism of N-methyl-D-aspartate receptors in the central nervous system may be also responsible for the intraoperative analgesic effect of magnesium. 5 The administration of magnesium sulphate also results in potentiation of the effects of neuromuscular blocking agents, mainly through inhibition of acetylcholine release at motor nerve terminals. 4 -7 The change in the balance between acetylcholine and rocuronium in the synaptic cleft results in the deepening of NMB.…”
mentioning
confidence: 99%